Seasonality of Stream Discharge and Leaf Litter Deposition in Kamalabogonan Creek, Candugay, Siaton, Negros Oriental - Raymundo, Laurie J. (Silliman Journal, 2024)
Stream discharge and leaf litter deposition data were collected for Kamalabogonan Creek, Candugay, Siaton, Negros Oriental, for January to December 1990. Discharge varied directly with monthly rainfall. Low values were recorded during the dry season (from January to May 1990), ranging from 0.09 m/min to 1.94m/min, with markedly higher values observed during, the rainy season (June to December 1990), ranging from 10.52 m?/min to 41.10 m*/min. Differences in leaf litter deposition into the stream were observed as well; deposition was generally higher and showed more fluctuation during the dry season (0.42 - 13.04 g dry weight/m?) while valyes obtained during the rainy season were less variable (1.95 - 8.81 g dry weight/m*). As leaf litter deposition represents a source of primary productivity for this stream via allochthanous input, quantification of the amount of input, the amount exported downstream, and the seasonality of input may lead to further understanding of the role of leaf litter in stream productivity.